Metal-polymer adhesion in plasma treated printed circuit boards - Laniog, Bryant N (2006)
This research aims to investigate the adhesion strength between the sputter deposited metal and the polymer based substrates, as a function of the type of metal deposited, substrates? surface conditions prior to deposition, chemical composition profiles across the bond region and the mechanical properties of the deposited metal. The polymer substrate used is a flame retardant-4 (FR-4) printed circuit board. Surface modification of the substrates were conducted using the Plasma Sputter Type Ion Source of the Plasma Physics Laboratory followed by metallization which was done in a RF magnetron sputtering system. The substrates were exposed to argon and oxygen plasma. Exposure time was set from a low of 90 seconds to a high of 12 minutes. After the modification, tiecoat and seedcoat metals were sputter deposited. The tiecoat metal used includes chromium, aluminum and copper. Thickness of the metal tiecoat (aluminum and chromium only) was set at 50A, 100A and 150A +5A. Experimental results were characterized by fourier transform-infrared spectroscopy, atomic force microscopy, scanning electron microscopy and energy dispersive spectroscopy. Adhesive properties were measured using the universal testing machine. The data obtained from the adhesion test were statistically analyzed to quantify adhesion test results. The surface morphology of the substrates changed substantially with ion dose and beam type after surface modification. Oxygen treatment caused the formation of larger surface flake-like microstructures compared to argon treatment. EDS data reveals that oxygen treated substrates has a higher relative percentage of oxygen in its surface, while longer exposure time means higher concentration of oxygen on the substrates? surface. Adhesion test results showed that high adhesion values came from the plasma treated substrates. Oxygen treated substrates produced higher adhesion strength compared to argon treated substrates. PCB substrates with longer plasma treatment exposure produced better adhesion. Chromium and aluminum tiecoats were found to provide improvement in adhesion strength. Chromium performed most effectively while copper deposited directly onto untreated PCB substrate could be easily removed. Metal tiecoat thickness does not affect adhesive property as conveyed by the statistical analysis. Moreover, plasma treatment resulted to increase in the adhesion strength of the metal-polymer interface by as much as 40 times higher than untreated substrate. Evidence of disrupted surface of the substrate after adhesion test indicates excellent metal adhesion and a tensile mode of failure within the PCB substrate. Two types of failure mechanisms were identified : adhesive failure at the PCB substrate/metal interface and tensile/cohesive failure in the PCB substrate itself. Tensile/cohesive failure in the PCB substrate was found to be the principal mode of failure for all the samples tested as supported by EDS analysis.
"March 2006."
Thesis (M.S. Materials Science & Engineering) - University of the Philippines Diliman.
Keywords: Polymers -- Surfaces; Adhesion